Potencial de Bacillus thuringiensis israelensis Berliner no controle de Aedes aegypti Potential of Bacillus thuringiensis israelensis Berliner for controlling Aedes aegypti - Ricardo Antonio Polanczyk; Marcelo de Oliveira Garcia; Sérgio Batista Alves (Universidade de São Paulo, 2003)
Relata-se a importância da bactéria entomopatogênica Bacillus thuringiensis israelensis para o controle de Aedes aegypti. São abordados a utilização e potencial de B. thuringiensis israelensis contra o mosquito vetor da dengue. Outros aspectos são discutidos como a evolução da resistência dos insetos em relação aos inseticidas químicos e as vantagens e desvantagens do controle microbiano como estratégia de controle. É dada ênfase à importância da utilização desta bactéria no Brasil como alternativa para resolver o problema em questão sem afetar o ambiente, o homem e outros vertebrados nas áreas de risco. The importance of the entomopathogenic bacterium Bacillus thuringiensis israelensis in the control of Aedes aegypti is presented. The use and potential of B. thuringiensis israelensis against the mosquito vector of dengue fever is described. Other aspects such as insect's resistance development against chemicals and advantages and constraints of using microbial control are discussed. Emphasis is given to the importance of the use of this bacterium in Brazil, which could contribute significantly to solving the mosquito problem without affecting the environment, humans and others invertebrate organisms in critical regions.